DETERMINING THE MARKET VALUE FOR AGRICULTURAL AND LIVESTOCK PROPERTIES - Silvia CHIOREAN; Tudor SĂLĂGEAN; Ioana Delia POP; Florica MATEI; Mircea VARGA; Mircea-Emil NAP (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Determining the market value for agricultural and livestock buildings involves considering various factors related to the structures, their functionality, and the overall agricultural market. The current trends and demand in the agricultural sector can influence property values. The geographical location of the property plays a significant role in determining its market value. The size and capacity of the buildings are also crucial factors. The impact of environmental factors, such as soil quality and climate conditions, on the property's productivity can influence its market value. The purpose of this work is to highlight the criteria that influence the market value for such a specialized property. In this study, nine plots of land, along with the agricultural and industrial buildings situated on them, located in Călărași County, Romania were the subject of valuation. For this, The Cost Approach was used. Also, within this method, a special importance is given to the estimation of the land’s market value, in this regard The Direct Comparison Method was utilized. In conclusion, it was observed that the largest percentage of the market value of the subject property comes from the buildings situated on the land plots and not from the free land.